MICROBIOLOGICAL AND CLINICAL FEATURES OF ODONTOGENIC INFECTIOUS ANAEROBIC ANALYSIS (World Bulletin of Public Health, 2025)
Odontogenic infections frequently exhibit a polymicrobial nature and may present with atypical clinical courses. Determining the microbial spectrum is essential for appropriate antimicrobial therapy and surgical management. This study aimed to investigate the microbial composition and clinical features of odontogenic infections in 90 patients using standardized aerobic and anaerobic culture techniques. Pus samples were collected aseptically by aspiration or immediately after surgical drainage, followed by quantitative culturing under aerobic and anaerobic conditions. All samples demonstrated bacterial growth. Staphylococcus species were most common (95.2%), dominated by coagulase-negative S. epidermidis (66.6%), while S. aureus was detected in 47.6% of cases. Streptococcaceae were found in 61.9% of patients, predominantly S. pyogenes. Anaerobic bacteria were present in 42.9%, and fungi were isolated in 19%. Enterobacteriaceae and Pseudomonas aeruginosa were not detected. Polymicrobial infections were observed in 90.5% of cases, mainly involving Staphylococcus–Streptococcus associations. Clinically, 22.9% of patients showed atypical infection courses, mostly males (64.4%) with a mean age of 38.6 ± 10.8 years. Odontogenic infections are argely polymicrobial with predominance of Gram-positive cocci and anaerobes. Accurate diagnosis requires both aerobic and anaerobic culture methods, and recognition of atypical cases is important for individualized treatment
Keywords: Odontogenic infection; polymicrobial infection; Staphylococcus